2018
DOI: 10.1097/brs.0000000000002740
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Internet Review Site Comments for Spine Surgeons

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…This generally favorable rating along with overall positive written comments is consistent with previous findings for orthopaedic surgeons as a whole as well as for those in other surgical fields. 17,19-22 Interestingly, a high percentage (84%) of the total number of ratings was either a 1-star (17% of total) or a 5-star (67%) rating. This pattern has been shown in previous studies and suggests that patients who perceive extremes of care are more likely to rate a physician online.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This generally favorable rating along with overall positive written comments is consistent with previous findings for orthopaedic surgeons as a whole as well as for those in other surgical fields. 17,19-22 Interestingly, a high percentage (84%) of the total number of ratings was either a 1-star (17% of total) or a 5-star (67%) rating. This pattern has been shown in previous studies and suggests that patients who perceive extremes of care are more likely to rate a physician online.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies that also found correlations between positive comments and surgeon-dependent factors (eg, surgical outcome, surgeon likeability/character). 20-22…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations